Criteria of selection of candidates for wrestling - Starosta, W.; Glaz, A. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
The selection of right candidates is crucial in every sport, including wrestling. Its correct solution ensures the development of the discipline itself and success for athletes. The increasing level of sport requires the participation of increasingly versatile wrestlers. Only such athletes can now be successful in the international arena. In some countries, natural selection was based on accepting all candidates and after some time rejecting those who did not achieve proper sports results. In most countries the selection was based on the checking of the candidates in respect to the various predispositions for wrestling. A number of different tests and trials were proposed for this purpose. It is not known which of these were scientifically verified and were used in a number of other countries. PURPOSE: of this study was: 1. An attempt to summarize the output collected in the criteria of selection of candidates for wrestling. 2. Presentation of the results of a pedagogical experiment aimed at determining the objectivity of tests in the selection of candidates for wrestling. 3. Presentation of own set of candidate selection tests for wrestling. RESULTS AND CONCLUSIONS: 1. The existence of a large number of proposals from various authors was found but none of them was checked for their reliability. 2. An annual pedagogical experiment was conducted on 121 persons, including 96 wrestlers and 25 children and using 13 anthropometric measurements and 7 fitness tests. Those wrestlers qualified for further training achieved higher scores in all tests used. Based on the results obtained, a set of fitness tests for the selection of candidates for wrestling was proposed. 3. Based on the 21-year long research conducted on wrestlers of the Polish National Team in the classic and free style, a set of 22 tests with high reliability ratios of the most important movement abilities necessary to achieve high sports results was developed. For the results of each test, a "T" scoring scale was developed to unify the results collected in different units and to evaluate the wrestler's performance level. 4. The proposed set includes tests to evaluate objectively the level of fitness required to be successful in all weight categories of wrestlers. Contemporary high requirements in this discipline regarding the coordination abilities required and their correct relationship to physical abilities were taken into account. 5. The table lists 7 sets of tests of performance for the evaluation of candidates for wrestling, including 3 own, which sum up the elaborations by for foreign and Polish authors. They allow the coach to select a set that is most suitable for specific club conditions.